Low temperature synthesis of ZnSe nanoparticles - Deshpande, Aparna; Singh, Shashi B.; Abyaneh, Majid Kazemian; Pasricha, Renu; Kulkarni, S. K. (Materials Letters, 2008)
Synthesis of thioglycerol capped zinc selenide nanoparticles with a relatively narrow size distribution by a simple and inexpensive low temperature (similar to 80 degrees C) wet chemical method is reported here. Main advantage of this method is the use of non-toxic precursors. The size of the nanoparticles can be varied easily by changing the concentration of the capping agent. The extracted nanoparticles remain stable under normal atmospheric conditions and can be redispersed in suitable solvents. The sharp absorption features obtained in the UV-Visible absorption spectra reveal the formation of monodispersed ZnSe nanoparticles. The nanoparticles were characterized using X-ray photoelectron spectroscopy, X-ray diffraction, UV-Visible absorption spectroscopy, photoluminescence and transmission electron microscopy. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Luminescence; Nanomaterials; Semiconductor; X-ray techniques